Effect of corrosion attack on the fatigue behavior of an as-cast Mg–7%Gd–5%Y–1%Nd–0.5%Zr alloy. (5th November 2015) - Wang, S.D.; Xu, D.K.; Wang, B.J.; Han, E.H.; Dong, C.
Abstract: Through investigating and comparing the fatigue behavior of an as-cast Mg–7%Gd–5%Y–1%Nd–0.5%Zr alloy in both laboratory air and 3.5 wt.% NaCl solution, the effect of corrosion attack on fatigue crack initiation has been disclosed. The S–N curves showed that the fatigue strength in air was 120 MPa and not sensitive to the loading frequency, whereas the fatigue strength in NaCl solution decreased from 80 MPa to 60 MPa with the loading frequency decreasing from 20 Hz to 5 Hz. Observations to fracture surfaces demonstrated that in air, fatigue cracks preferentially initiated at the oxide inclusions. However, the fatigue crack initiation in NaCl solution was associated with corrosion pits. Moreover, multiple fatigue cracks initiated at pits on fracture surfaces of corrosion fatigue failed samples when the loading frequency decreased to 5 Hz. Based on the measured "defect area" of oxide inclusions, the predicted fatigue strength in air could be well fitted with the experimental data. However, due to the occurrence of hydrogen embrittlement and crack initiation at multiple sites, the fatigue strength of samples tested in NaCl solution cannot be predicted. Graphical abstract: Highlights: Degradation of corrosion fatigue strength is sensitive to the loading frequency. Fatigue crack initiation at pits is due to the occurrence of hydrogen embrittlement. Fatigue strength in air can be predicted based on the measured "defect area".